A niche‐based gap analysis for the conservation of odonate species in the Brazilian Amazon. Issue 5 (14th April 2021) - Brasil, Leandro Schlemmer; de Andrade, André Felipe Alves; Ribeiro, Bruno R.; Spigoloni, Zander A.; Juen, Leandro; De Marco, Paulo
Abstract: Despite the current rates of deforestation and the expected climatic changes, protecting species in their natural habitats is still the simplest, cheapest, and most effective way of safeguarding biodiversity. Here, the network of protected areas in the Brazilian Amazon was evaluated to assess its effectiveness in safeguarding species of Odonata. Ecological niche models were built to assess the suitability of the habitat for 503 Amazonian odonate species. Then, the effectiveness for the protection of odonate species of three classes of protected areas (strictly protected area, sustainable use area, and indigenous territory) was evaluated. Approximately 30% of the species are protected within the network of protected areas. These findings highlight the importance of protected areas for safeguarding most odonate species in the Amazon. For under‐represented or gap species, additional resources are still needed for effective management and protection on some private properties, which need to set aside land for conservation. In this way, it is possible to preserve habitats for odonate species and guarantee their conservation in the Amazon.